Maize productivity cultivated as first crop in succession to different cover crops - Anselmo, Jefferson Luis; Bossolani, João William [UNESP]; Lazarini, Edson [UNESP]; Leal, Aguinaldo Jose Freitas; Alvarez, Rita de Cássia Félix; Arf, Marcelo Valentini (Southern Cross Publishing, 2018)
The plant residues left on the soil surface in no-tillage systems are an important source of nutrients for the subsequent crops, particularly under tropical climate. The aim of this study was to evaluate the cover plants grown during the off-season on development and productivity of maize cultivated in the first crop in no-tillage system. The experiment was conducted in the 2010/11 and 2011/12 agricultural years, in the experimental area. The experimental delineation used was the random blocks with four repetitions and eight treatments (as cover crops) consisted as follows: maize (alone), maize + Urochloa ruziziensis, sorghum, Crotalaria spectabilis, Urochloa ruziziensis, forage turnip, millet and fallow. The cover plants were placed in Litter Bags, which were fixed to the ground in each plot and collected at 0, 15, 45, 75 and 115 days after the handling of the covers. Plant height, first ear insertion height and grain productivity were assessed in the culture of maize. Maize in single cropping or intercropping with Urochloa ruziziensis were good option to cover plants for the no-tillage system, due to maintenance of straw on the soil surface. Maize seeded on crop residues of C. spectabilis and U. ruziziensis showed more plant height; crop residues of forage and U. ruziziensis provided an increase maize culture productivity grown in succession.
Keywords: Cerrado; Direct seeding; Zea mays